3D bioprinting for artificial cornea: Challenges and perspectives. (September 2019) - Zhang, Bin; Xue, Qian; Li, Jintao; Ma, Liang; Yao, Yufeng; Ye, Hua; Cui, Zhanfeng; Yang, Huayong
Highlights: The progress, applications and limitations of most influential works among current keratoprosthesis and tissue-engineering cornea researches are discussed in this review. The development stages and guideline of corneal substitutes are suggested in this review. The potential, advantages in current research of 3D bioprinting single or multi-layer corneal equivalents and alternatives are discussed. An insight into the value, challenges and potential applications of 3D bioprinting methods in corneal substitutes manufacturing are enumerated and analyzed. Abstract: Corneal disease is one of the most important causes of blindness worldwide. Currently, the dominating treatment of corneal blindness is corneal transplantation. However, the main source of cornea for transplantation is based on donations which is far from enough to meet the requirement (less than 1:70 of cases). The severe shortage of donor cornea promotes the studies of effective corneal alternatives. However, many problems remain and can't be solved in current researches, such as original geometry reconstruction and ocular optical function restoring. 3D bioprinting can be a promising approach for corneal substitution. The advantages of this technology in corneal regeneration enable personalized corneal implant and single or multi-layer corneal equivalents with controllable structure and designed refractive ability. In this review, the progress, applications and limitations of most influential works among current keratoprosthesis and tissue-engineering cornea researches are discussed. Then the applications of 3D bioprinting in manufacturing multi-layered structures and surface are mentioned. Further, the potential, advantages in current research of 3D bioprinting single or multi-layer corneal equivalents and alternatives are discussed. Finally, an insight into the technical challenges and prospective facing the future research of 3D bioprinting corneal alternatives in vivo and in vitro is provided.